Recent Developments in the Physical Adsorption of Toxic Organic Vapours by Activated Carbons - Robert H. Bradley (Adsorption Science & Technology)
Active, or microporous, carbons are established and effective adsorbents for toxic and other organic vapour-phase compounds. Their porosity results predominantly from slit-shaped pores of molecular dimensions (and hence widths < 2 nm) formed by spaces between graphene layers in a turbostratic structure. They are used in a wide range of separation and recovery processes where adequate performance is often routinely achieved using relatively cheap, generic active carbons (ACs) produced from precursors such as coal, nutshells and wood. However, many current, or new, applications require more refined properties, such as greater selectivity or specific surface chemistry, before the full potential of ACs can be realized. Typical examples occur in separations associated with toxic organic compounds, for example in industrial and military respiratory protection or effluent clean-up, where the removal of highly toxic or noxious vapour species, sometimes present at very low concentrations, is required from atmospheric air streams which contain near-saturation pressures of water vapour. In this instance, a hydrophobic carbon with a pore structure which is optimized to the target species is required to solve this problem, but other applications, for example to control other emissions to the environment (SO x /NO x /Hg) or in energy storage (H 2 /CH 4 ) and electrochemical double-layer capacitance (EDLC) usage, may require quite different properties. Against this background, it is not surprising that there is currently great interest in active carbons with controllable properties and increased adsorption performance to meet these new challenges. Research workers are now looking beyond conventional ACs to materials with very specific properties which are tailored to meet these more exacting high-performance applications. However, in turn, achieving these goals places greater emphasis on both accurate structure/property characterization and also upon methods by which adsorption properties can be manipulated. In this review, the basic structure and properties of ACs are presented in relation to their adsorption characteristics; this is accompanied by an overview of adsorption theories which underpin quantitative equilibrium isotherm analysis (Polanyi–Dubinin–Stoeckli, Sing-α S , DFT) and allow the derivation of detailed physical and chemical information about carbon adsorbents, and comparison and understanding of the adsorption behaviour of target vapour species. Emphasis is placed on the types of interactions which occur between vapour molecules and the carbon surfaces, and the relative energy of these interactions. Consideration is given to the non-specific (London-type) forces which occur between vapour molecules and graphene basal planes, and the enhancement of these forces, between these planes and within micropores (width < 2 nm), leading to the Type I isotherms characteristic of these carbons. The size of vapour molecules relative to the (slit) width of pores is also discussed, as is the effect of the presence of wider (> 2 nm) pores. In contrast, specific interactions occurring at polar sites, and therefore dominated by the surface chemistry of the carbon structure, are also reviewed; critical in this respect are the interactions which occur between surface oxygen-containing groups — which are mainly present on the edge sites of the carbon planes — and water molecules, the competitive adsorption of which may seriously limit the adsorption of target species in many separation applications which are carried out in humid environments. Discussion of these aspects is followed by some comments on adsorption kinetics and dynamic filtration and, to emphasize the theoretical points which arise, examples are given of how manipulation of carbon characteristics can begin to be used to control and optimize adsorption for a range of more challenging applications.